2019
DOI: 10.4102/jef.v12i1.202
|View full text |Cite
|
Sign up to set email alerts
|

Exchange market pressure in South Africa and Kenya: An analysis using parametric and non-parametric extreme value theory

Abstract: Exchange market pressure (EMP) is the selling pressure of domestic currency or excess demand needed for foreign currency. Research purpose:The purpose of this study was to analyse EMP using extreme value theory (EVT) and to compare two commonly used EVT methods. Motivation for the study:To determine whether the EMP of two African countries can be modelled with EVT, and if so, which method would be best suited. To determine periods of extreme pressure or currency crisis by using these methods. Lastly, to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Further findings indicated that in the longrun, financial openness heightened the impact of EMP. Boer, et al [34] adopt Peak over Threshold (POT) ARMA/ARCH/GARCH result revealed that the positive nature of the parameters was a confirmation to the generalized extreme value distributions. Abtahi and Bioki [35] adopted the Threshold Vector Autoregressive (TVAR) and the Markov-Switching Vector Autoregressive (MS-VAR) models as its method of estimation and findings revealed that the lag of the parameters exerted no significant effects on EMP under a low inflation regime, with a significant impact resulting under a high inflation regime.…”
Section: Empirical Literaturementioning
confidence: 94%
“…Further findings indicated that in the longrun, financial openness heightened the impact of EMP. Boer, et al [34] adopt Peak over Threshold (POT) ARMA/ARCH/GARCH result revealed that the positive nature of the parameters was a confirmation to the generalized extreme value distributions. Abtahi and Bioki [35] adopted the Threshold Vector Autoregressive (TVAR) and the Markov-Switching Vector Autoregressive (MS-VAR) models as its method of estimation and findings revealed that the lag of the parameters exerted no significant effects on EMP under a low inflation regime, with a significant impact resulting under a high inflation regime.…”
Section: Empirical Literaturementioning
confidence: 94%